Barriers To The Utilization Of Primary Care Services For Mental Health Problems Among Adolescent In A Secondary School In Malaysia. - Aida Jaffar; Noor Azimah Muhammad; Tuti Iryani Mohd Daud; Ramli Musa; Khairani Omar; Mohd Radzniwan A Rashid (Academy of Family Physicians of Malaysia, 2024)
Indexed by Scopus